The interactions of algae-activated sludge symbiotic system and its effects on wastewater treatment and lipid accumulation. (November 2019) - Chen, Xingyu; Hu, Zhan; Qi, Yun; Song, Chunfeng; Chen, Guanyi
Highlights: The co-culture of Scenedesmus sp. 336 and activated sludge in light performed best. The symbiotic systems showed notably higher NO3 − -N removal than the sterile cultures. Gas exchange, oxidative stress and IAA secretion contributed to the enhancement. Microbial analysis showed the role of denitrifying bacteria and PGPB in symbiosis. Abstract: The ability of Scenedesmus sp. 336, Chlorella sp. 1602 and activated sludge (AS) alone or in combination to remove nutrients and accumulate lipid in artificial municipal wastewater under light/dark conditions was studied. The symbiotic systems showed greater advantages than the sterile systems. Scenedesmus sp. 336 + AS system obtained the highest lipid productivity after seven days of cultivation in light, while the NO3 − -N and COD were completely absorbed and utilized, as well as the removal rate of PO4 3− -P and NH4 + -N were 99.82% and 87.13%, respectively. Total superoxide dismutase (SOD) activity was measured to demonstrate the relationship between oxidative stress and lipid accumulation. Besides, the results of microbial analysis showed that some dominant plant growth-promoting bacteria could secrete indole-3-acetic acid (IAA) to enhance the interaction between algae and bacteria, and the denitrifying bacteria that could coexist with microalgae also improved the efficiency of wastewater treatment in the symbiotic systems.